Strength simulation of rock with existing cracks under static loadings - Chea, Bunly. (2009)
This report presents a model for the strength simulation of rock for static loading condition. The random cracks have been assigned within the rock sample and the crack percentages are laid between zero percent to five percents. The simulation of the rock sample with pre-existing microcracks is observed in action of applied compression force. The basic analysis is based on the results obtain from DDA (Discontinuous Deformation Analysis Simulations. The initial joints properties are uniform, but due to pre-existing microcracks, certain joints property possesses low value that indicates the location of weak joints.